2017
DOI: 10.4172/2157-7013.1000268
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Alpha and Inflammation-Mediated Cardiac Injury

Abstract: Experimental evidence is accumulating implicating a major role for inflammatory activation in chronic heart failure. Levels of pro-inflammatory protein mediators, such as tumor necrosis factor-alpha (TNF-α), a pro inflammatory cytokine, have been shown to be elevated in heart failure patients and appear to be directly related to pathological changes in the myocardium. Unfortunately, outcomes from clinical trials using anti-cytokine therapies to chronic heart failure patients have been largely disappointing. TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(55 reference statements)
0
5
0
1
Order By: Relevance
“…However, TNFR2 induces an anti-inflammatory effect to counter the effects of TNFR1 on tissue repair. In the clinic, TNF-α levels are known to increase and TNF-α receptors are known to significantly decrease in patients with chronic heart failure [ 46 ]. Therefore, variations in TNFR1 and TNFR2 signaling and regulation during cardiac disorders remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, TNFR2 induces an anti-inflammatory effect to counter the effects of TNFR1 on tissue repair. In the clinic, TNF-α levels are known to increase and TNF-α receptors are known to significantly decrease in patients with chronic heart failure [ 46 ]. Therefore, variations in TNFR1 and TNFR2 signaling and regulation during cardiac disorders remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The results of present study shows that a significant increase in serum level of IL-8, MCP-1 and TNF-α observed during the infection with E. histolytica, which reflect a pro-inflammatory role of these cytokines in the infection [13,14,15]. Trophozoite attachment to host epithelial and inflammatory cells and to colonic mucins and bacteria is mediated by a lectin specific for galactose/N-acetyl-galactosamine [16,17,18].…”
Section: Discussionmentioning
confidence: 50%
“…Thus, TNF-α has been used for malignant disease treatment since beginning of the twentieth century. Ever since the discovery of TNF-α, it has been comprehensively studied for its involvement in acute and chronic inflammation, cell differentiation and proliferation, stimulation of programs of cellular suicide including apoptosis and necroptosis, cell metabolism, autoimmune diseases and cancer [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in host defense against microbial infections, control of cell survival and proliferation and efficient antitumor activities. It is also called cachectin, endotoxin-induced factor in serum, or differentiation-inducing factor [ 3 , 4 , 5 ]. This cytokine is secreted from activated macrophages, monocytes and natural killer (NK) cells in response to any immunological challenge [ 2 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%